A flow-circulation system incorporating a PVP-BiOBr@rGO assembly for simultaneous degradation and detection of oxytetracycline in fish farm wastewater - Teerasong, Saowapak; Suknakhin, Nichakarn; Sonsaket, Thanamat; Teerasong, Wanatchaporn; Ruttanapun, Chesta; Sriwong, Chaval; Chompoosor, Apiwat; Nanan, Suwat (My University, 2025)
This work focuses on developing a new flow-circulation system for simultaneous detection and degradation of oxytetracycline (OTC) in fish farm wastewater to address a need for antibiotic abatement in wastewater treatment. Polyvinyl pyrrolidone capped bismuth oxybromide assembled with a reduced graphene oxide (PVP-BiOBr@rGO) photocatalyst was solvothermally synthesized and characterized. The prepared photocatalyst exhibited a morphological flower-like structure with a high surface area, 47.59 m2 g−1. Its band gap energy was 2.93 eV. A ternary PVP-BiOBr@rGO composite showed lower charge recombination than its pure form. PVP-BiOBr@rGO was filled inside a catalyst column of a flow system, with a spectrophotometer at the column end. Wastewater was continuously transported through the column and OTC spectrophotometrically examined during its degradation. The wastewater was recirculated until the OTC concentration was minimized. This system achieved 90.3% degradation of OTC within 180 min. The catalyst column could be regenerated for 2 cycles. The proposed flow system offers the advantages of ease of use, inline operation, and real-time sensing. This highlights a potential for real-world sustainable wastewater treatment applications.